Hyperglycosylated hCG activates LH/hCG-receptor with lower activity than hCG. (5th January 2019) - Koistinen, Hannu; Koel, Mariann; Peters, Maire; Rinken, Ago; Lundin, Karolina; Tuuri, Timo; Tapanainen, Juha S.; Alfthan, Henrik; Salumets, Andres; Stenman, Ulf-Håkan; Lavogina, Darja
Abstract: While human chorionic gonadotropin (hCG) appears to have an essential role in early pregnancy, it is controversial whether the hyperglycosylated form of hCG (hCG-h), which is the major hCG isoform during the first 4–5 weeks of pregnancy, is able to activate LH/hCG receptor (LHCGR). To address this, we utilized different extensively characterized hCG and hCGβ reference reagents, cell culture- and urine-derived hCG-h preparations, and an in vitro reporter system for LHCGR activation. The WHO hCG reference reagent (99/688) was found to activate LHCGR with an EC 50 -value of 3.3 ± 0.6 pmol/L (n = 9). All three studied hCG-h preparations were also able to activate LHCGR, but with a lower potency ( EC 50 -values between 7.1 ± 0.5 and 14 ± 3 pmol/L, n = 5–11, for all P  < 0.05 as compared to the hCG reference). The activities of commercial urinary hCG (Pregnyl) and recombinant hCG (Ovitrelle) preparations were intermediate between those of the hCG reference and the hCG-h. These results strongly suggest that the hCG-h is functionally similar to hCG, although it has lower potency for LHCGR activation. Whether this explains the reduced proportion of hCG-h to hCG reported in patients developing early onset pre-eclampsia or those having early pregnancy loss remains to be determined. Graphical abstract: Image 1 Highlights: Hyperglycosylated hCG (hCG-h) is able to activate LH/hCG receptor (LHCGR). hCG-h has lower potency than hCG for (LHCGR) activation. Kinetics of LHCGR activation was slower with hCG-h than with hCG. Proteolytically processed hCG (hCGn) had low, if any, potency for LHCGR activation.